"Let’s say they are talking about Madrid" - Guerrero González-Valerio, Beatriz; Ramírez Barredo, Belén (Street Art & Urban Creativity, 2025)
Documentary photography in Spain has been a powerful tool for capturing identity and culture in different historical contexts. Spanish photographers have used this medium to represent and explore the reality of their time, becoming increasingly aware of the subjectivity of their vision. At the same time, there is a growing need for photographers to show their individuality, their own style, tending more and more towards the reportage of the author. This is the context of two national photography prizes: Cristina García Rodero (Puertollano, 1949) National Photography Prize in 1996 and Alberto García Alix (León, 1956), winner in 1999. In their personal vision of Madrid, both coincide in directing their gaze at its inhabitants, for as the writer Antonio Muñoz Molina points out, ‘In Madrid there is almost no other landscape than the human landscape, which is the privileged territory of photography’ (2020). .